Norway's economy Maintaining a successful business sector in a changing world - Hemmings, Philip (OECD Publishing, 2018)
Norway's success in maintaining high living standards, low inequality and good progress in gender balance owes much to its business sector. High-productivity business-sector jobs support high wages and profits, providing capacity to fund comprehensive public services and inclusive employment practices. Ensuring that the business sector thrives as globalisation and technologies evolve further and as the oil and gas sector enters long-term decline requires maintaining business-friendly conditions. This paper examines framework conditions, notably competition legislation and policy affecting firm entry and exit ("firm dynamics"). It evaluates how best to encourage new business models, as well the growing issue of labour supply among older cohorts. Education policy's role in providing skills conducive to good lifetime earnings is also discussed
Keywords: Economics; Norway